Patients with Central Hypothyroidism are Less Sufficiently Treated with Levothyroxine than Patients with Primary Hypothyroidism - Samec, Barbara; Setnikar, Gaja; Gaberscek, Simona; Kocjan, Tomaz (Experimental and Clinical Endocrinology & Diabetes, 2021)
Background Contrary to patients with hypothyroidism after radioiodine (HRI) or after thyroidectomy (HTh), patients with central hypothyroidism (CH) cannot rely on thyrotropin (TSH) level to guide their treatment with L-thyroxine (L-T4). Consequently, they are at constant risk of under- or overtreatment. We aimed to establish the adequacy of L-T4 treatment in patients with CH in our cohort.Methods Consecutive patients with CH on L-T4 treatment were compared with patients adequately treated for HRI or HTh. Levels of free thyroxine (fT4) and free triiodothyronine (fT3) were evaluated and the fT4/fT3 ratio was calculated.Results Forty patients with CH, 136 patients with HRI and 43 patients with HTh were included in this study. Patients with HRI were significantly younger than patients with HTh and CH (p<0.001 for both). Levels of fT4 were significantly lower in CH than in adequately treated patients with HRI and HTh (median (range), 15.6 (12.7–21.3), 18.4 (12.2–28.8), and 18.7 (13.8–25.5) pmol/L, respectively, p<0.001 for both comparisons). Levels of fT3 did not differ significantly (p=0.521) between CH, HRI and HTh (median (range), 4.5 (2.7–5.9), 4.3 (3.2–6.2), and 4.4 (2.9–5.5) pmol/L, respectively). Accordingly, the fT4/fT3 ratio was significantly lower in the CH group than in HRI and HTh groups (median (range), 3.7 (2.5–5.2), 4.2 (1.2–7.7), and 4.4 (2.5–6.1), respectively, p<0.001 for both comparisons).Conclusions Patients with CH have lower fT4 levels and lower fT4/fT3 ratios than patients adequately treated for HRI or HTh. The cause for this difference may be the unreliable TSH levels in patients with CH.
Keywords: Primary hypothyroidism; Radioiodine therapy; Thyroidectomy; Central hypothyroidism